Impact of perceived threats, benefits, and athlete brand image on attitudes toward naturalized athletes in the context of China - Lu, Haixiang; Liu, Dongfeng; Pu, Haozhou; Persaud, Alan Robert (Frontiers in Psychology, 2024)
Introduction China’s implementation of athletic naturalization has sparked controversy, yet empirical studies on the factors influencing public attitudes toward naturalized athletes remain scarce. This study aims to address this gap by constructing a theoretical model based on social identity theory, examining the impact of various psychological variables on respondents’ attitudes toward naturalized athletes in China’s national teams. Methods Data were collected from 704 online respondents. Descriptive and exploratory factor analyses (EFA) were conducted using SPSS 25.0. Structural equation modeling with partial least squares (PLS-SEM) was employed to test the proposed hypotheses, utilizing SmartPLS 3.0. Results The findings indicate that perceived threats negatively impact attitudes (β = −0.134, p < 0.001), while perceived benefits positively influence athlete brand image (β = 0.494, p < 0.001) and attitudes (β = 0.169, p < 0.001). Athlete brand image positively affects attitudes (β = 0.623, p < 0.01) and mediates the relationship between perceived benefits and attitudes. Additionally, sport event involvement positively moderates the relationship between athlete brand image and attitudes. The model explained 33.7% of the variance in athlete brand image and 68.5% of the variance in attitudes. Discussion These findings suggest that naturalization decisions should consider the candidates’ overall brand image, with the naturalization process being more transparent and the naturalized athletes’ contribution being effectively communicated to the public. Additionally, fostering public involvement in sport events can create a more favorable atmosphere for athletic naturalization.